FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN BERAT BADAN LAHIR RENDAH DI WILAYAH KERJA PUSKESMAS BANGETAYU KOTA SEMARANG TAHUN 2016 - Fatima Anggi Jayanti; Yudhy Dharmawan; Ronny Aruben (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2017)
Low birth weight (LBW) is one of causes to baby mortality throught the world which reaches 20 times of world mortality. The aim of this research is analizing factors which are in line with LBW in Public Health Centre of Bangetayu, Semarang City. This is a descriptive research with unpaired case control design. The samples of the research are 43 respondents of mothers bearing a low weight birth baby as a case data and 43 respondents of matohers a normal birth weight baby as control data. The data are analized by chi-square test. The result shows that there is a significant relation between age (CI=1,922-11,891 ; OR=4,780); wieght (CI=2,284-16,162 ; OR=6,076); and preterm gestational age (CI=1,647-10,553 ; OR=4,168) and is also becoming risk factors. Moreover, the relation between abortion report (CI=0,244-9,695 ; OR=1,538); distance of pregnancy (CI=0,839-5,227 ; OR=2,095); upper arm circumference (LILA) (CI=0,989-7,672 ; OR=2,755); family income (CI=0,454-2,714 ; OR=1,110); education (CI=0,542-3,943 ; OR=1,462); and accupation (CI=0,935-9,255 ; OR=2,942) shows no significant relation and is not becoming risk factors. This also happen to parity (CI=0,263-1,621 ; OR=0,653); medical record (CI=0,197-1,902 ; OR=0,613); systole blood pressure (CI=0,154-3,482 ; OR=0,731); and diastole blood pressure (CI=0,103-4,101 ; OR=0,650) that show no significant relation and is not becoming risk factors but protective factors with low birth weight. The researcher recommends parents to take care of their pregnancy, especially those who are in high-risk age, and weight increase. It is also suggested that parents intensively do antenatal care to detect a complication in very early. The mothers with high-risk pregnancy are also suggested to undergo a regularly medical check up for monitoring the growth of the baby.